First faunal inventory of large branchiopods (Crustacea: Branchiopoda) of Western Maharashtra, India with taxonomical and distributional comments - Padhye, Sameer; Rabet, Nicolas; Ghate, Hemant (Zootaxa, 2015)
An updated inventory of large branchiopods of the Western Maharashtra state, India is presented for the first time. Employing current identification keys, we have detailed the egg morphology of Eulimnadia indocylindrova, which shares some similarities with E. geayi from South America and E. alluaudi from Madagascar, based on these egg characters. A thorough re-description of few morphological traits of the same species is also presented. We also have described the female of a Cyzicus species seen rarely from the studied region. Distributional comments on few species are also reported.